Manajemen Strategis Pengembangan Kinerja Pemerintah Daerah Kabupaten Polewali Mandar - Erni Eka Pratiwi; Haris Maupa; Muhammad Ismail (Magister Management, Hasanuddin University, 2019)
This study aims to analyze the strategic management of regional government performance development Polewali Mandar. The type of data used in this study is quantitative and qualitative data. Data sources used are primary data and secondary data. The population in this study is the West Sulawesi provincial government apparatus, sampling using a purposive sampling method, with a sample that is the West Sulawesi Provincial Government apparatus. Analyzed data was performed using SPPS for Windows Version 20. The results of this study indicate that all proposed variables have a positive and significant influence on the performance of Polewali Mandar District Government employees, in this case showing that the strategy implemented by the government is very helpful in improving or developing employee performance. The results of the correlation of the three variables indicate that these three variables are still weak to be able to support employee performance improvement, so it is important to add variables or conduct research on variables that can still be used as a strategy to improve employee performance.